2012
DOI: 10.4103/0019-509x.107728
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco use in Nepal

Abstract: Tobacco use is widely prevalent in different forms in Nepal. These habits are deeply rooted among different age groups and gender. There is no information available on all aspects of smokeless tobacco (SLT) use and its implications in Nepal. To review the types of SLT products available in Nepal, prevalence of SLT use, correlates of SLT use, SLT-related harm, and existing gaps in information and policy implications. This review is mainly based on information from literature, and some WHO and other documents. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…Low prevalence of smoking and SLT use among women as reported earlier [17],[34] is not surprising since it is socially unacceptable for women to smoke in South Asian communities [36]. However, SLT use was common in India, Nepal, and Cambodia, confirming the results of previous studies [11],[37]. …”
Section: Discussionsupporting
confidence: 84%
“…Low prevalence of smoking and SLT use among women as reported earlier [17],[34] is not surprising since it is socially unacceptable for women to smoke in South Asian communities [36]. However, SLT use was common in India, Nepal, and Cambodia, confirming the results of previous studies [11],[37]. …”
Section: Discussionsupporting
confidence: 84%
“…Among 10 significant factors (sociodemographic as well as family and childhood environmental factors) in univariate analysis, only four factors demonstrated significant association with smoking susceptibility ( P <0.05). The model was statistical significant, that is, there was a significant relationship between smoking susceptibility and family and childhood environmental factors (LR chi 24=38.36, Prob>Chi-square (4)<0.001) and therefore all other family and childhood risk factors including sex were dropped from the model (for P >0.05 and P <0.1). The highest adjusted R 2 was 0.18 indicating that collinearity was not present among the risk factors included in the model.…”
Section: Resultsmentioning
confidence: 99%
“…A study from India revealed that tobacco advertisements significantly influenced the use of tobacco products among adolescents (47), despite bans against tobacco advertising (17). Similarly, Nepal has banned tobacco advertisements since 1998 but ineffective implementation of policies results in continuous exposure of adolescents (3, 4). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Similarly, Nepal Adolescents and Youth Survey (NAYS) published in 2012 revealed 13% of adolescents and youth ever used smoking or smokeless tobacco and 6% used illicit drugs. [4] As noted by Sinha et al [5] in 2012, prevalence of smokeless tobacco was 18.6% among adults aged 15-64 years; 31.2% among males and 4.6% among females. 'A study conducted comparing the tobacco use among youth of Bangladesh, Nepal and Srilanka revealed prevalence is high in Nepal (9.4%) than Bangladesh (6.9%) and Srilanka (9.1%) but the age of initiation of tobacco use was the highest among Nepali youth (10.24 yrs.)…”
Section: Introductionmentioning
confidence: 86%